INOKULASI MIKORIZA VESIKULA ARBUSKULA (MVA) CAMPURAN SEBAGAI PENGENDALI PENYAKIT LAYU FUSARIUM PADA TANAMAN SEMANGKA (Citrullus vulgaris Schard) - Saniyatun Mar’atus Solihah; Uki Dwiputranto; Purnomowati Purnomowati (Agritech: Jurnal Fakultas Pertanian Universitas Muhammadiyah Purwokerto, 2013)
A research aimed to examine the effect of dosage interaction and MVA inoculation technique on the incidence of fusarium wilt in watermelon plants has been carried out. Method used was experimental with a Complete Randomized Design (CRD) in a factorial pattern. The first factor was MVA treatment in four levels, i.e. M0 (no MVA given), M1 (MVA = 7.5 g/plant), M2 (MVA = 10 g/plant), M3 (MVA = 12.5 g/plant). Whereas, the second factor was different inoculation techniques: IbJ (VAM was inoculated when seeds were planted) and Ibt (VAM was inoculated when the seedlings were replanted). The main parameter in this research was the incubation period and disease intensity, while the supporting parameters were VAM infection intensity, soil pH, air temperature and relative humidity. Obtained data of the disease intensity and the incubation period were analyzed with analysis of variance (F test) and continued with Least Significant Differences test with the error level of 5%. Results indicated that the interaction of dosages and mixed MVA inoculation technique had suppressed the disease intensity and delayed the incubation period of fusarium wilt in watermelon plants, while the dosages of mixed MVA separately affected the intensity and delayed the incubation period of fusarium wilt in watermelon plants. The mixed MVA dosege of 10 g/plant was the most effective to suppress Fusarium wilt disease intensity in watermelon plants, while the dosage of 12.5 g/plant was the best to delay the incubation period of fusarium wilt in watermelon plants. Key words : inoculation of MVA and Fusarium Wilt Disease